2017
DOI: 10.1253/circj.cj-17-0195
|View full text |Cite
|
Sign up to set email alerts
|

Automated Ablation Annotation Algorithm Reduces Re-conduction of Isolated Pulmonary Vein and Improves Outcome After Catheter Ablation for Atrial Fibrillation

Abstract: VISITAG Module) uses an algorithm for the automated annotation of RF ablation applications based on objective, predefined parameters. Because it provides crucial information on catheter stability and ablation intensity at each site, it may be helpful in accomplishing durable PVI.The aim of this study was therefore to evaluate the utility of automated ablation lesion annotation by comparing procedure parameters and outcomes between automated annotation-guided and non-guided procedures. Methods SubjectsThe study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…20 Our study is unique because it uses an automated radiofrequency application display module, which integrates CF with catheter stability and ablation time, thus allowing quantitative control of the lesion set at the PV antrum. 21 In fact, the PVAM group (including the two subgroups) demonstrated a more adequate contact control than the CPVI group.…”
Section: Pvam Versus Cpvi: Pv Antrum Substrate Modification Contributmentioning
confidence: 93%
See 1 more Smart Citation
“…20 Our study is unique because it uses an automated radiofrequency application display module, which integrates CF with catheter stability and ablation time, thus allowing quantitative control of the lesion set at the PV antrum. 21 In fact, the PVAM group (including the two subgroups) demonstrated a more adequate contact control than the CPVI group.…”
Section: Pvam Versus Cpvi: Pv Antrum Substrate Modification Contributmentioning
confidence: 93%
“…To date, there have been few clinical trials dedicated to the investigation of the use of an automated module in the ablation of AF. 21 Our ablation setting was a comprehensive consideration for safety and efficacy based on previous data regarding the CF setting and the corporation recommendations. [25][26][27][28] With CF, lesions can be quantitatively deployed, and the lesion size can be reliably assessed.…”
Section: Technique Considerations For Pvam Using the Cf Cathetermentioning
confidence: 99%
“…The RF lesion quality is determined based on predefined parameters of stability, time, and CF. Several studies have shown that PVI guided by automatic annotation of RF tags is associated with higher acute success rate and better long‐term outcomes compared with conventional PVI . It has been proposed that RF applications that meet automatic annotation criteria achieve greater lesion durability .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PVI guided by automatic annotation of RF tags is associated with higher acute success rate and better long-term outcomes compared with conventional PVI. 13,17 It has been proposed that RF applications that meet automatic annotation criteria achieve greater lesion durability. 13 However, it has not been shown that conventional applications are associated with a higher risk of late PVR.…”
Section: Automatic Acquisition Of Rf Tags As a Marker Of Lesion Qualimentioning
confidence: 99%
“…The 3D mapping systems with automatic lesion index integration of contact‐force feedback help to visualize and evaluate the efficiency and stability of lesions along the ablation line . Additionally, AF ablation with contact‐force technology and strict criteria of stability was reported as a safe procedure and is associated with an improvement in efficiency and a reduction in AF recurrence …”
Section: Chapter 7: Three‐dimensional Mapping‐guided Catheter Ablatiomentioning
confidence: 99%